Trade, wages, and profits - Hartmut Egger; Peter Egger; Udo Kreickemeier (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper formulates a structural empirical model of heterogeneous firms whose workers exhibit fair-wage preferences, leading to a link between a firm's operating profits and wages of workers employed by this firm. We estimate the parameters of the model in a data-set of five European economies. The model predicts an exporter wage premium, which we find to be sizable in all countries, with nearly 10 percent on average. The estimates enable us to conduct counterfactual exercises. We find that openness to international trade has quantitatively important effects, leading to higher wage inequality and lower aggregate employment.
Keywords: C31; F12; F16; J31; 330; structural models; heterogeneous firms; fair wages; labour market imperfections; exporter wage premium